Photocurable resin composition

A photopolymerizable resin composition with aliphatic urethane (meta) acrylate and additives enhances adhesion and heel mark resistance while preventing cracking in vinyl chloride flooring, addressing surface damage and processing issues.

JP2025015061APending Publication Date: 2025-01-30AICA KOGYO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023118161
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Existing vinyl chloride flooring materials face issues with surface damage, heel mark resistance, and cracking during cutting and processing, necessitating a coating that enhances scratch resistance and maintains integrity during shaping.

Method used

A photopolymerizable resin composition comprising aliphatic urethane (meta) acrylate, phosphate compound, reactive diluent, and photopolymerization initiator, with optional silicone (meta) acrylate monomer, is used to create a coating that improves adhesion, heel mark resistance, and prevents cracking during cutting.

Benefits of technology

The composition ensures sufficient adhesion, good heel mark properties, and prevents cracking during cutting, making it suitable for PVC tiles and other plastic flooring applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015061000001
    Figure 2025015061000001
  • Figure 2025015061000002
    Figure 2025015061000002
  • Figure 2025015061000003
    Figure 2025015061000003
Patent Text Reader

Abstract

To provide a photocurable resin composition characterized by superior heel mark resistance, superior cutting processability, and reduced risk of cracking during cutting.SOLUTION: A photocurable resin composition contains an allophanate-type urethane (meth)acrylate, a phosphoester compound, a reactive diluent, and a photopolymerization initiator. The content of the urethane (meth)acrylate is 30-60 wt.% relative to the total solid content.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photocurable resin composition which is used by curing it with ultraviolet light or the like. [Background technology]

[0002] Plastic flooring materials are used in a wide range of buildings, from office buildings and commercial facilities to ordinary homes. Among these plastic flooring materials, vinyl resin flooring materials, including polyvinyl chloride, are relatively inexpensive and easy to install, and have many excellent properties such as chemical resistance, abrasion resistance, scratch resistance, flexibility, and ability to conform to the substrate, so they are used in a wide range of places, including schools, hospitals, factories, and government facilities.

[0003] For example, vinyl tiles are a typical example of vinyl flooring. While cushioned flooring, which is also made of polyvinyl chloride, is soft and not very durable, and is easily dented or worn down by the legs of tables and chairs, vinyl tiles have a moderate hardness and durability. They are also cheaper and easier to install than wooden or ceramic flooring materials, and can be made thinner than these, so they have the advantage of not interfering with door opening and closing or thresholds even when installed directly on existing flooring.

[0004] Due to these advantages, PVC tiles are used in a wide range of fields. On the other hand, although they are relatively hard, their surfaces are easily scratched and worn, so that they are often coated with a coating agent that improves their resistance to scratches and heel marks. For example, PVC tiles that form a glassy inorganic protective coating layer on their surface have been proposed (Patent Document 1). However, the harder the coating layer, the lower the cutting processability when processing into a tile shape, and the more likely it is to crack. Therefore, there has been a demand for a well-balanced coating agent that has sufficient resistance to scratches and heel marks, while at the same time causing very little cracking of the coating layer when cutting. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6065247 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a photocurable resin composition which has good heel mark resistance, good cutting processability and is less likely to crack when cut. [Means for solving the problem]

[0007] In order to solve the above problems, the invention described in claim 1 provides a photocurable resin composition comprising an allophanate-type urethane (meth)acrylate (A), a phosphate ester compound (B), a reactive diluent (C), and a photopolymerization initiator (D), wherein the blending amount of (A) is 30 to 60% by weight based on the total solid content.

[0008] The invention according to claim 2 provides the photocurable resin composition according to claim 1, further comprising a silicone-modified (meth)acrylate monomer (E).

[0009] The invention as set forth in claim 3 provides the photocurable resin composition as set forth in either claim 1 or claim 2, which is a coating agent for a polyvinyl chloride substrate.

[0010] The invention according to claim 4 provides a building material coated with the photocurable resin composition according to claim 1 or 2. Effect of the Invention

[0011] The photocurable resin composition of the present invention has sufficient adhesion to the substrate, good heel mark resistance, and good cutting processability with little cracking when cut, making it useful as a coating agent for plastic flooring materials such as PVC tiles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below.

[0013] The composition of the present invention comprises an allophanate-type urethane (meth)acrylate (A), a phosphoric acid ester compound (B), a reactive diluent (C), and a photopolymerization initiator (D). In this specification, the term "(meth)acrylate" includes both acrylate and methacrylate.

[0014] The allophanate-type urethane (meth)acrylate (A) used in the present invention is one of the main components that make up the cured coating, and has abrasion resistance and toughness due to the cohesive force of hydrogen bonds derived from urethane bonds. It has an allophanate bond (-NH-CO-NCOO- group) in which a urethane bond has reacted with an isocyanate group, and the interaction of hydrogen bonds between OH groups, which has a significant effect on viscosity, becomes intramolecular, making it possible to reduce the viscosity compared to urethane (meth)acrylates of the same structure that do not have allophanate bonds. In addition, it has good curing properties with a fast curing speed and no stickiness, and is characterized by high hardness and low curing shrinkage.

[0015] The number of functional groups of (A) is preferably 2 to 8, more preferably 4 to 6. By making it 2 or more functional, sufficient curability and adhesion to the adherend can be ensured, and by making it 8 or less functional, cure shrinkage during curing can be reduced and cutting processability can be stabilized. In addition, when it has a polyester-modified skeleton, it is preferable because heel mark resistance can be further improved.

[0016] The weight molecular weight (hereinafter referred to as Mw) of (A) is preferably 1,000 to 20,000, more preferably 3,000 to 15,000, and particularly preferably 5,000 to 10,000. By making it 1,000 or more, the cohesive force of the cured product can be sufficiently ensured, and by making it 20,000 or less, the composition viscosity can be easily adjusted to a suitable level for workability. Note that Mw was measured and calculated by gel permeation chromatography using a column with a styrene-divinylbenzene-based packing material and a tetrahydrofuran eluent as the molecular weight in terms of standard polystyrene.

[0017] The blending amount of the (A) is 30 to 60% by weight, preferably 32 to 55% by weight, and more preferably 35 to 50% by weight, based on the total solid content. If it is less than 30% by weight, the cutting processability tends to decrease, and if it exceeds 60% by weight, it becomes difficult to adjust the viscosity to a level suitable for application, and the leveling property may also decrease.

[0018] The phosphoric acid ester compound (B) used in the present invention is blended for the purpose of improving the adhesive strength with the substrate. A (meth)acrylate monomer having a phosphoric acid ester group is preferable in terms of compatibility with (A) and excellent curing properties. For example, 2-(meth)acryloyloxyethyl dihydrophosphate, dipentaerythritol penta(meth)acryloyloxydihydrogen phosphate, etc. are included. In particular, bis[2-(methacryloyloxy)ethyl] hydrogen phosphate of the following chemical formula (1), which is generated by the reaction of 2-hydroxyethyl methacrylate with phosphoric anhydride, is preferable. Chemical formula (1) JPEG2025015061000001.jpg3355

[0019] The amount of (B) is preferably 0.3 to 5.0% by weight, more preferably 0.5 to 3.0% by weight, based on the total solid content. By adding it in this range, the adhesive strength with the substrate can be improved. Commercially available (meth)acrylate monomers having a phosphate ester group include KAYAMER PM-2 and PM-21 (trade names: manufactured by Nippon Kayaku Co., Ltd.).

[0020] The reactive diluent (C) used in the present invention is blended for the purpose of lowering the viscosity of the composition and improving the curability. In terms of suppressing cure shrinkage, it is preferably trifunctional or less, and more preferably monofunctional. For example, examples of chain alkyl monomers include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; examples of alicyclic monomers include cyclohexyl (meth)acrylate and isobornyl (meth)acrylate; examples of monomers having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 3-hydroxyethyl (meth)acrylate, and 4-hydroxyethyl (meth)acrylate. Examples of the monomers having an aromatic ring include benzyl (meth)acrylate, phenoxyethyl acrylate, and methylphenoxyethyl acrylate. Examples of the amide compounds include N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, and acryloylmorpholine. These can be used alone or in combination of two or more. Among these, hydroxyl group-containing (meth)acrylates are preferred in terms of improving adhesion to vinyl chloride, and 2-hydroxypropyl methacrylate, which has good compatibility with (A) and (B) and is highly dilutable, is even more preferred.

[0021] The amount of (C) is preferably 10 to 50% by weight, more preferably 20 to 40% by weight, and particularly preferably 25 to 35% by weight, based on the total solid content. By making it 10% by weight or more, it is possible to expect adjustment to a viscosity with excellent workability and at the same time ensure sufficient curing properties, and by making it 50% by weight or less, good cutting processability can be ensured.

[0022] The photopolymerization initiator (D) used in the present invention generates radicals when irradiated with ultraviolet light or an electron beam, and the radicals trigger the polymerization reaction, and general-purpose photopolymerization initiators such as benzyl ketal, acetophenone, and phosphine oxide photopolymerization initiators can be used. By arbitrarily selecting the light absorption wavelength of the polymerization initiator, it is possible to impart curability over a wide wavelength range from the ultraviolet region to the visible light region. Specifically, 2.2-dimethoxy-1.2-diphenylethan-1-one is a benzyl ketal, 1-hydroxy-cyclohexyl-phenyl-ketone and 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one are α-hydroxyacetophenones, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one are α-aminoacetophenones, and 2.4.6-trimethylbenzoyl-diphenyl-phosphine oxide and bis(2.4.6-trimethylbenzoyl)-phenylphosphine oxide are acylphosphine oxides, which may be used alone or in combination of two or more. Among these, it is preferable to use α-hydroxyacetophenones, which are less prone to yellowing.

[0023] The amount of (D) is preferably 2 to 15 parts by weight, more preferably 5 to 10 parts by weight, per 100 parts by weight of the photopolymerizable component. By adding 2 parts by weight or more, sufficient curability can be ensured, and by adding 15 parts by weight or less, an excessive amount is not added, and sufficient molecular weight can be ensured even after curing. Commercially available α-hydroxyacetophenone products include JRCURE1103 (trade name: manufactured by Daido Chemical Industry Co., Ltd.).

[0024] In the present invention, it is preferable to further contain a silicone-modified (meth)acrylate monomer (E). By blending (E), heel mark resistance can be stably improved. For example, urethane (meth)acrylate having a silicone skeleton can be mentioned. The Mw of (E) is preferably 1,000 to 20,000, more preferably 3,000 to 15,000. By setting it in this range, heel mark resistance can be sufficiently improved.

[0025] The amount of (E) is preferably 30% by weight or less, more preferably 20% by weight or less, and particularly preferably 15% by weight or less, based on the total solid content of the composition. By making it 30% by weight or less, it is possible to improve heel mark resistance and cutting processability in a well-balanced manner.

[0026] In addition, additives such as leveling agents, inorganic fillers, surfactants, tackifiers, antioxidants, ultraviolet absorbers, flame retardants, defoamers, wettability adjusters, organic fine particles, and antistatic agents can be used in combination with the photocurable resin composition of the present invention (hereinafter referred to as the present composition) within the scope that does not impair the performance.

[0027] The leveling agent can improve the leveling properties during coating and can also improve the scratch resistance and stain resistance of the cured coating. Examples of the leveling agent include fluorine-based, silicone-based, and fluorine silicone-based agents, and can be used alone or in combination of two or more types.

[0028] Among these, silicone-based polysiloxane compounds that can equalize the large surface tension difference on the coating film surface are preferred. Examples include polyalkyl siloxanes, polyaryl siloxanes, polyalkylaryl siloxanes, polyester-modified siloxanes, polyether-modified siloxanes, etc., which can be used alone or in combination of two or more kinds.

[0029] The amount of the leveling agent is preferably 0.1 to 3% by weight, more preferably 0.3 to 2% by weight, based on the total solid content. By setting the amount within this range, sufficient leveling properties can be ensured, and the coating film can have a stable appearance, while improving scratch resistance and antifouling properties. Commercially available products include TEGO Glide 410 (trade name: polyether-modified siloxane copolymer, manufactured by EVONIK INDUSTRIES).

[0030] The inorganic filler can improve the appearance of the coating film and the hardness of the cured coating film. Examples of the inorganic filler include silica particles, alumina particles, and titanium oxide particles, and can be used alone or in combination of two or more kinds. By blending the component, light is diffusely reflected, and the gloss of the coating film surface can be suppressed. In addition, in order to improve adhesion to the coating film, it is preferable to treat the surface with an organic component.

[0031] In particular, when adjusting the glossiness of the coating film appearance, it is preferable to blend amorphous silica with a secondary particle size of 0.5 to 10 μm. Also, by blending silica with a polyethylene-treated surface, a very smooth matte surface can be obtained. The blending amount depends on the desired glossiness, but for example, 1 to 20% by weight based on the total solid content is exemplified. Commercially available products include ACEMATT OK607 (trade name: manufactured by EVONIK INDUSTRIES, secondary particle size 4.4 μm, surface polyethylene-treated), etc.

[0032] The composition may be diluted with a solvent. However, in the case of a substrate that is highly soluble in polar solvents such as vinyl chloride, it is preferable to use a solvent with low polarity. The blending amount is preferably 10% or less, and more preferably solvent-free. In the present invention, "solvent-free" means excluding intentional blending of a solvent for the purpose of dilution, and does not mean excluding even trace amounts of volatile components contained in each component of the composition, and refers to a solvent content of 5% by weight or less, typically 1% by weight or less.

[0033] The method for applying the composition is not particularly limited and may be any known method. When applying to the entire surface of an adherend, for example, a roll coater, a reverse roll coater, a knife coater, an air knife coater, a bar coater, a slot die coater, a lip coater, a gravure coater, a reverse gravure coater, etc. may be used.

[0034] The composition can be used as a coating material for plastic materials. In particular, when used as a coating agent for the surface of polyvinyl chloride tiles, it is suitable because it has excellent heel mark resistance and the coating film is less likely to crack during cutting.

[0035] The composition is applied to a substrate and then cured using light such as ultraviolet light. Examples of light sources include low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, carbon arc lamps, xenon lamps, metal halide lamps, LED lamps, and electrodeless ultraviolet lamps. The curing conditions are 50 mW / cm. 2 ~3000mW / cm 2 The irradiation intensity is 100 to 2,000 mJ / cm2 as the cumulative light quantity. 2 The irradiation atmosphere may be air or an inert gas such as nitrogen or argon.

[0036] The storage modulus of the cured product obtained by photocuring the composition is preferably 600 MPa or less, more preferably 500 MPa or less, at 30° C., and preferably 230 MPa or less, more preferably 200 MPa or less, at 40° C. By keeping the storage modulus within this range, sufficiently stable cutting processability can be ensured.

[0037] The present invention will be described in detail below based on examples and comparative examples, but these are specific examples and are not intended to be limiting. Unless otherwise specified, measurements were performed under conditions of room temperature of 25°C and relative humidity of 65%. The blend amounts are in parts by weight.

[0038] Examples 1 to 7 (A) UreaC 1 (pentafunctional allophanate type polyester modified urethane acrylate, Mw 8,000, solid content 100%) and UreaC 2 (pentafunctional allophanate type urethane acrylate, Mw 7,000, solid content 100%), (B) KAYAMER PM-2 (trade name: manufactured by Nippon Kayaku Co., Ltd.), (C) Light Ester HOP(N) (trade name: manufactured by Kyoeisha Chemical Co., Ltd., hydroxypropyl methacrylate), (D) JRCURE1103 (trade name: manufactured by Daido Chemical Industry Co., Ltd., α-hydroxyacetophenone type), (E) MIRAMER SIU2400 (trade name: MIWON, 10-functional silicone urethane acrylate, Mw 8,000, solid content 100%), UreaC A (2-functional polytetramethylene glycol skeleton urethane acrylate, Mw 2,500, solid content 100%) as an oligomer, TEGOGlide 410 (trade name: EVONIK INDUSTRIES, polyether modified siloxane copolymer, solid content 100%) as a leveling agent, and ACEMATT OK607 (trade name: EVONIK INDUSTRIES, secondary particle diameter 4.4 μm amorphous silica, surface polyethylene treatment) as a filler were used, and the mixture was stirred until uniformly dissolved in the formulation shown in Table 1 to prepare the photocurable resin compositions (solventless) of Examples 1 to 7.

[0039] Comparative Examples 1 to 4 In addition to the materials used in Example 1, UreaC B (difunctional caprolactone-skeleton urethane acrylate, Mw 2,000, solids 100%) and UreaC C (difunctional polyester-skeleton urethane acrylate, Mw 7,000, solids 100%) were used as oligomers, and the resulting mixture was stirred until uniformly dissolved according to the formulation shown in Table 2 to prepare photocurable resin compositions (solventless) for Comparative Examples 1 to 4.

[0040] Table 1 JPEG2025015061000002.jpg113159

[0041] Table 2 JPEG2025015061000003.jpg142137

[0042] The evaluation method was as follows.

[0043] Curing: The photocurable resin composition was applied to an unpainted PVC tile with a thickness of 3 mm to a film thickness of 20 μm, and the composition was irradiated with an electrode high-pressure mercury lamp (product name: iGrandage ECS4011GX / N, manufactured by iGraphics Co., Ltd.) at an irradiation intensity of 100 mW / cm 2 , cumulative light intensity 800mJ / cm 2 The coating film was irradiated with ultraviolet light at 400 nm and the tackiness of the coating film surface was checked. Those that were cured without tackiness were rated as ◯, and those that were tacky but not cured were rated as x.

[0044] Adhesion: According to JIS K5600-5-6, a 10x10 grid of 1mm squares was created and a cross-cut test was performed, and the peeling state of the coating film was confirmed using cellophane tape (specified in JIS Z1522). When the cellophane tape attached to the coating film side was peeled off, if 0 squares peeled off, it was marked as ○, and if even 1 square peeled off, it was marked as ×.

[0045] Glossiness: According to JIS Z 8741, the 60° glossiness was measured using Micro Trigloss (manufactured by Byk-Gardner Co., Ltd.).

[0046] Heel mark resistance: Using a heel mark tester conforming to JIS K3920, six standard rubber blocks were used, and the test was run for 3,000 revolutions at 50 revolutions per minute to evaluate the initial adhesion of heel marks and their removability. The evaluation method for initial adhesion was as follows: ◎ if there were almost no adhesion marks, ◯ if there were slight adhesion marks, and × if there were dark adhesion marks. Regarding dirt removability, ◎ if the adhesion marks could be completely removed with a cloth, ◯ if there were slight adhesion marks remaining, and × if they could not be removed at all.

[0047] Cutting processability: The coating was applied to an unpainted PVC tile with a thickness of 3 mm so that the dry film thickness was 20 μm, and the coating was applied using an electrode high-pressure mercury lamp (product name: iGrandage ECS4011GX / N, manufactured by iGraphics Co., Ltd.) with an irradiation intensity of 100 mW / cm 2 , cumulative light intensity 800mJ / cm 2The test specimen was then returned to room temperature and placed in a 40°C thermostatic chamber for at least 3 hours, after which it was punched out using a No. 3 dumbbell from the test specimen heated to 40°C, and the cross section was observed under an electron microscope at 150x magnification. If no cracks were found in the coating, they were marked with an ◯, and if cracks were found, they were marked with an X.

[0048] Storage modulus: Using a TA instruments DMAQ800, the storage modulus was measured at 30°C and 40°C using a sample of the resin composition 5 mm wide and 200 μm thick cured with the above UV device under conditions of an illuminance of 100 mW / cm2 and an accumulated light quantity of 800 mJ / cm2.

[0049] Table 3 JPEG2025015061000004.jpg73135

[0050] Table 4 JPEG2025015061000005.jpg129155

[0051] The resin compositions of the Examples showed good results in the evaluations of curability, adhesion, heel mark resistance, and cutting processability. In all Examples, the storage modulus was 500 MPa or less at 30°C and 200 MPa or less at 40°C.

[0052] On the other hand, Comparative Example 1, which did not contain (B), had poor adhesion, Comparative Examples 2 and 3, which used ureac that was not of the allophanate type, had poor cutting processability, and Comparative Example 4 had poor heel mark resistance, and none of these were suitable for the present invention.

Claims

1. A photocurable resin composition comprising an allophanate-type urethane (meth)acrylate (A), a phosphoric acid ester compound (B), a reactive diluent (C), and a photopolymerization initiator (D), the amount of (A) being 30 to 60% by weight based on the total solid content.

2. 2. The photocurable resin composition according to claim 1, further comprising a silicone-modified (meth)acrylate monomer (E).

3. 3. The photocurable resin composition according to claim 1, which is a coating agent for a polyvinyl chloride substrate.

4. A building material coated with the photocurable resin composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Air-fuel ratio controlling method in internal- combustion engine

    JP1985065247A